Analisa Pemilihan Moda Angkutan Antara Angkutan Online dan Angkutan Konvensional (Studi Kasus Angkot Trayek LDG) - Jehamin, Artoldus; Arifianto, Andy Kristafi; Oktaviastuti, Blima (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
Respondents' choice of the means of transportation they use to get there is based on its reliability, safety, and comfort. In Malang City, especially in LDG, where internet travel is more common than traditional travel, this is a major cause of transportation problems. The impact can be seen in the decline in users of conventional transportation because people prefer the comfort and convenience offered by online transportation. Knowing what characteristics online and traditional transportation users on the LDG route in the city of Malang have is the aim of this research. This type of descriptive research uses a quantitative research design. The client statistical index (CSI) approach, with the help of SPSS 25 software, was used for data analysis in this research. The survey was carried out by distributing questionnaires to 50 online transportation respondents and 50 conventional transportation respondents, containing the characteristics of travellers based on age group, gender, job group, and income group. The results of this research are the characteristics of travellers at a percentage of 54% with age <26 years choosing online transportation, gender with a percentage of men 80% women 20%, occupational group at a percentage of 34% choosing online transportation, and income group 1,000,000-2,500. 000 at a percentage of 44% choosing online transportation. Following that, 54% of respondents over 25 years old chose conventional transportation, then 54% of men and 46% of women. Teachers made up 22% of the occupational group that chose conventional transportation, and 44% of respondents in the 1,000,000 to 2,500,000 income group chose conventional transportation.